2018
DOI: 10.3324/haematol.2018.191569
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo evaluation of possible pro-survival activities of PGE2, EGF, TPO and FLT3L on human hematopoiesis

Abstract: Myelosuppression is a major and frequently dose-limiting side effect of anticancer therapy and is responsible for most treatment-related morbidity and mortality. In addition, repeated cycles of DNA damage and cell death of hematopoietic stem and progenitor cells, followed by compensatory proliferation and selection pressure, lead to genomic instability and pave the way for therapy-related myelodysplastic syndromes and secondary acute myeloid leukemia. Protection of hematopoietic stem and progenitor cells from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Since loss of human HSPC was not complete, it is very likely that other anti-apoptotic BCL-2 proteins, especially MCL-1, have an important role in HSPC survival 5,49 . Regarding the in vivo data, it should be kept in mind that xenograft models are of only limited feasibility in testing function and stress resistance of human stem cells 50 . Xenotransplantation comes along with incompatibility between human HSCs and the murine microenvironment, thereby imposing very high levels of stress on the transplanted cells.…”
Section: Discussionmentioning
confidence: 99%
“…Since loss of human HSPC was not complete, it is very likely that other anti-apoptotic BCL-2 proteins, especially MCL-1, have an important role in HSPC survival 5,49 . Regarding the in vivo data, it should be kept in mind that xenograft models are of only limited feasibility in testing function and stress resistance of human stem cells 50 . Xenotransplantation comes along with incompatibility between human HSCs and the murine microenvironment, thereby imposing very high levels of stress on the transplanted cells.…”
Section: Discussionmentioning
confidence: 99%
“…The roasted Astragalus and stir-fried Atractylodes macrocephala Koidz in Erzhu Yiren Decoction invigorate the spleen and replenish Qi, and the stir-fried Squid Bone and Bletilla striata yield an excellent acid-inhibiting effect. Moreover, the combination with Lily with a moisturizing effect succeeds in replenishing Qi and invigorating the spleen, clearing away heat and dampness, and eventually yields a gastric-protective efficacy [26,27]. Therefore, the effective rate of gastroscopic ulcer healing in the observation group was significantly higher than that of the control group (P < 0:05), and the clinical symptom score after treatment was significantly lower than that of the control group (P < 0:001), indicating significantly improved gastric ulcer after the introduction of Erzhu Yiren Decoction.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous reports, 1.5-3.5 Gy doses of χ-ray radiation have been used before leukemia cell [18][19][20] or CD34 + cells [21,22] transplantation into mice, but only a few studies did not use irradiation [23]; for example, Shafat et al reported the successful construction of a primary AML model with nonirradiated NSG mice [24]. In this study, we explored the radiation dose in model construction.…”
Section: Discussionmentioning
confidence: 99%